The New Humanists: Literary and Cinematic Reactions to the End of the Postmodern Era. - Jaffe, Maxwell P. (Tufts Archival Research Center, 2005)
A look into literary and cinematic reactions to Postmodernism. Authors such as David Foster Wallace, Jonathan Franzen, and Denis Johnson are examined alongside filmmakers Charlie Kaufman, Spike Jonze, Michel Gondry, and Gus Van Sant. These /New Humanists/" react to and look beyond postmodernism ultimately forming an entirely new literary movement. "